Burden of Disease, Unmet Needs in the Diagnosis and Management of Atopic Dermatitis: An Indian Expert Consensus - Rajagopalan M (Dove Medical Press, 2021)
Murlidhar Rajagopalan,1 Amar Jeet Chitkara,2 Samir Dalwai,3 Abhishek De,4 Ram Gulati,5 Samipa Mukherjee,6 Sharad Mutalik,7 Nidhi Sharma,8 Shrutakirthi Shenoi,9 Prakash Vaidya,10 Amod Tilak,11 Charles Adhav11 1Department of Dermatology, Apollo Hospitals, Chennai, Tamil Nadu, India; 2Department of Pediatrics, Max Super Specialty Hospital, Shalimar Bagh, Delhi, India; 3New Horizons Child Development Center, Mumbai, Maharashtra, India; 4Department of Dermatology, Calcutta National Medical College, Kolkata, West Bengal, India; 5SDM Hospital, Jaipur, Rajasthan, India; 6Cloudnine Hospitals, Bengaluru, Karnataka, India; 7Department of Dermatology, Maharashtra Medical Foundation, Pune, Maharashtra, India; 8Medanta Hospital, Gurugram, Haryana, India; 9Department of Dermatology, Kanachur Institute of Medical Sciences, Mangaluru, Karnataka, India; 10Department of Pediatrics and Neonatology, Fortis Hospital, Mulund, Maharashtra, India; 11Pfizer India Ltd., Pfizer Biopharmaceuticals Group (Emerging Markets), Mumbai, IndiaCorrespondence: Murlidhar RajagopalanDepartment of Dermatology, Apollo Hospitals, Chennai, Tamil Nadu, IndiaTel +91 9840045500Email murlilata@gmail.comBackground: Atopic dermatitis (AD) is a chronic inflammatory, non-communicable, and relapsing skin disease that affects all age groups. There is a dearth of literature that reports the disease burden, and epidemiology and highlights unmet needs in the diagnosis and management of AD in India.Methods: A total of ten specialists including dermatologists, pediatric dermatologists, and pediatricians with more than ten years of experience and practicing in different parts of India served as the expert panel during the virtual meet conducted on January 24, 2021. A questionnaire comprising 32 questions on different aspects of AD management was categorized among different sections: burden of disease (five questions), age of onset and prevalence (five questions), etiology and pathogenesis (six questions), diagnosis and severity of the disease (seven questions), and treatment (nine questions). Consensus was defined when agreement was provided by ≥ 90% of the experts.Results: Considering the profound impact AD has on the quality of life (QoL) of patients, the expert panel recommended patient counseling while moderate to severe cases of AD need a prompt referral to a specialist. The panel did not recommend any specific diagnostic and severity criteria as a standard due to the inherent limitations associated with every criterion. The role of environment and changing lifestyle in addition to genetic and familial risk factors for AD was also considered. The panel unanimously recommended to conduct a countrywide, multicenter survey/study to estimate the true prevalence of AD in India. Further, the experts recommended to follow proper treatment protocols and to perform longitudinal monitoring for understanding corticosteroid treatment associated side effects.Conclusion: This guidance focuses on identifying the unmet gaps and provides practical recommendations for improving QoL, diagnosis, prognosis, and overall management of patients with AD in India.Keywords: consensus development, cost of illness, dermatologist, epidemiology, pediatrician, quality of life